Coastal Lab Anak Nelayan di Desa Lasitae Kabupaten Barru: Belajar, Berkarya, Melestarikan - Musrayani Usman; Ainun Jariah Yusuf; Andi Annisar Dzati Iffah; Mario Mario; Nadya Elvira; Nur Annisa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The Coastal Lab for Fishers’ Children program was developed to address limited access to non-formal education, the absence of cultural expression spaces, and low ecological literacy in the coastal community of Lasitae Village, Barru Regency. Activities were conducted from June to September 2025 using a Participatory Action Research (PAR) approach that positioned children, parents, community leaders, and volunteers as active subjects from planning through reflection. Core interventions included: interactive reading classes and a marine-themed literacy corner (contextual literacy), art workshops/art corner (maritime cultural expression), and conservation education (simple experiments, a Mini Waste Bank, and coastal campaigns). Evaluation employed pre–post tests, participatory observation, attendance logs, and FGDs, analyzed using descriptive–thematic methods. Findings indicate substantial improvements in knowledge (55.4%→81.5%; ↑46.9%), skills (57.8%→84.3%; ↑45.8%), and community participation (35.4%→79.0%; ↑43.6%). In addition, social capital was fostered, marked by increased family logistical support, learning assistance, and participation in beach festivals and children’s art exhibitions (≥20 works). In the ecological domain, the Mini Waste Bank collected approximately 125 kg of sorted waste in three months and spurred household waste segregation adoption (>70% of respondents). The results affirm that a community-based learning model integrating literacy, arts, and conservation within a PAR framework effectively enhances cognitive, affective, and social outcomes while cultivating ownership and sustainability through village policy. The model is recommended for replication in other coastal villages with strengthened local cadres and triple helix partnerships.